Black snake : Standing Rock, the Dakota Access Pipeline, and environmental justice - Todrys, Katherine Wiltenburg (University of Nebraska Press, 2021)
"Black Snake" tells the story of the controversial Dakota Access Pipeline through the influential activism of four women from Standing Rock and Fort Berthold Reservations"--